1980
DOI: 10.1111/j.1365-3032.1980.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

The imaginal ecdysis of the desert locust, Schistocerca gregaria.

Abstract: ABSTRACT. The imaginal ecdysis of the desert locust, Schistocerca gregaria (Fo̊rsk.), is described in detail. Ecdysis is considered to begin when the fifth instar nymph ceases to feed and to end when the adult takes its first meal. It is here divided into six stages: Stages 1 and 2 constitute the pre‐emergence behaviour; Stages 3 and 4, emergence; Stage 5, the expansion of the new cuticle; and Stage 6, the post‐expansional behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…For example, studies on insect ecdysis (i.e. moult) found that failure of ecdysis appears to occur because of disruption of muscle contractions that are involved in working the individual forward out of the old cuticle (Hughes, 1980; Ewer et al , 1997; Park et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies on insect ecdysis (i.e. moult) found that failure of ecdysis appears to occur because of disruption of muscle contractions that are involved in working the individual forward out of the old cuticle (Hughes, 1980; Ewer et al , 1997; Park et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Molt strategy was recorded as a binary indicator: 0 = normal or 1 = extra molting. We assessed the maximal nymphal weight rather than the weight at adult emergence since the fifth instar nymph/young fledged adult ceases to feed and looses weight 24-48h before/after imaginal molt [ 56 ]. We also studied the probability of survival at each development stadia (nymphal stadia, first adult week).…”
Section: Methodsmentioning
confidence: 99%
“…Locust foregut movements are responsible for passing food particles from the pharynx to the crop, and also for pumping air to inflate the alimentary canal at early stages of the molt (Hughes, 1980 ; Ayali, 2004 , 2009 ; Zilberstein et al, 2006 ). Although the gut has some intrinsic contractile capabilities (Oldfield and Huddart, 1982 ; Banner et al, 1987 ), foregut movements are under the control of the stomatogastric nervous system (STNS), which is comprised of a small set of peripheral ganglia (Figure 1 ): the frontal ganglion (FG), the hypocerebral ganglion (HG), and the paired ingluvial ganglia (IG; Chapman, 1998 ).…”
Section: Introductionmentioning
confidence: 99%